Networks of imperial tropical medicine: ideas and practices of health and hygiene in the British Empire, 1895-1914 - Johnson, R; Ryan M Johnson (2009)
This thesis investigates several previously neglected networks of imperial tropical medicine (ITM) in Britain and its tropical colonies at the turn of the twentieth-century. It argues for the need to bring back the ‘imperial’ to the study of medicine in colonial localities; and, in doing so, redefines the ‘imperial’ in relation to tropical medicine during this period. To accomplish this, the first part of the thesis considers largely ignored popular networks of ITM, including the 1900 London Livingstone Exhibition; guidebooks and manuals for tropical travel, health and hygiene; and commodities such as Burroughs Wellcome & Co.’s (BWC) Tabloid brand medicine chests and tropical clothing. The second part of the thesis investigates important, but under researched professional networks of ITM, including the training and experiences of non-medical missionaries educated at Livingstone College, London and the London Missionary School of Medicine (LMSM); and the formation and reform of the West African Medical Staff (WAMS). All of the popular and professional networks discussed in this thesis were, for the most part, a response to the urgency generated by domestic and international high politics to ‘improve’ and ‘develop’ Britain’s tropical possessions. While representing a diversity of individuals and interests, one concern that they all shared was the supposed need to preserve Anglo-Saxon health in tropical climates. Such a disparate set of ‘agents of empire’, connected through a common interest, led to a complex set of ideas and practices of ITM, which were informed as much by the environment and climate, as new disciplines such as parasitology. This thesis also demonstrates that a significant fissure existed — within and outside the imperial state — between ideas of ITM and their practice. Ideas of ITM were often aggressively imperial in rhetoric but in practice they generally were not. Therefore, at the start of the twentieth-century ITM was not always working — directly — as a ‘tool of empire’. Nonetheless, this thesis demonstrates that the ‘imperial’ is still the most useful analytical category and organising principle for understanding Western medicine’s relationship to Britain’s tropical possessions during this period. By focusing on both the colony and the metropole, and the uneven power relationship that existed between them, it demonstrates that ideas and practices of medicine and hygiene intended for Britain’s tropical empire were neither colonial nor metropolitan, but imperial.